2006
DOI: 10.1590/s0102-05362006000400011
|View full text |Cite
|
Sign up to set email alerts
|

Características de produção de frutos de melancia sem sementes em função de fontes e doses de potássio

Abstract: página do horticultorN o Brasil, a produção de melancia sem sementes é ainda incipiente. Embora algumas pequenas áreas comerciais tenham sido implantadas em São Paulo, Rio Grande do Sul e Rio Grande do Norte acredita-se que será neste últi-mo Estado que a produção de melancia sem sementes irá se concentrar (Schiavon Jr., Comunicação pessoal). O menor tamanho do fruto, característica que facilita o transporte e acondicionamento, e a ausência de sementes, explorada comercialmente pelas empresas como novidade de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(1 reference statement)
0
2
1
2
Order By: Relevance
“…Different from the present study, Grangeiro & Cecílio Filho (2006) observed that the yield of seedless watermelon showed a quadratic behavior in response to K doses. The maximum yield was estimated at 20,400 kg ha -1 , for the K 2 O dose of 183 kg ha -1 .…”
Section: Resultscontrasting
confidence: 99%
“…Different from the present study, Grangeiro & Cecílio Filho (2006) observed that the yield of seedless watermelon showed a quadratic behavior in response to K doses. The maximum yield was estimated at 20,400 kg ha -1 , for the K 2 O dose of 183 kg ha -1 .…”
Section: Resultscontrasting
confidence: 99%
“…O incremento da produtividade de melancieira com aumento de doses de potássio no solo também foi verificado por Grangeiro & Cecílio Filho (2006), El-Bassiony et al (2012, Oliveira et al (2012). O rendimento máximo obtido, 23 t ha -1 , é superior aos valores 9,4 e 21,1 t ha -1 registrados por Grangeiro & Cecilio Filho (2006) e Rashidi & Kesharvazpour (2011), respectivamente, em plantas de melancia cultivadas em solo com fornecimento de K e N. Em plantas de melancia tratadas com N e P, Uwah et al (2010) obtiveram um valor máximo de 18 t ha -1 .…”
Section: Resultsunclassified
“…) e observaram variação significativa na massa média dos frutos. Em outros trabalhos realizados porGrangeiro & Cecílio Filho (2006) e El-Bassiony et al(2012), onde utilizou-se doses variando entre 50 e 300 kg ha -1 também foi observada variação significativa para doses de K sobre a massa média dos frutos. Isso significa que a dose, 30 kg ha…”
unclassified
“…The supply of potassium and nitrogen to the soil in addition to manure stimulated fruit production. These two nutrients are required in large amounts by watermelon (Grangeiro & Cecílio Filho, 2006), and therefore plants responded positively to their supply. Leão et al (2008) evaluated the effects of applying manure and NPK fertilizer on watermelon production, and obtained 1.15 fruits per plant by providing 9 L manure per hole, treatments with fertilization.…”
Section: Resultsmentioning
confidence: 99%
“…Fertilization is a crucial factor for short-cycle vegetable crops with a high demand for nutrients like potassium and nitrogen (Andrade Junior et al, 2006). Some studies show that watermelon is highly demanding of potassium, the nutrient that is the most absorbed and exported to the fruits during the productive phase (Grangeiro & Cecílio Filho, 2006;Aguyoh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%